Chilling injury of tomato fruit was alleviated under low-temperature storage by silencing Sly-miR171e with short tandem target mimic technology - Zhao, Keyan; Chen, Rulong; Duan, Wenhui; Meng, Lanhuan; Song, Hongmiao; Wang, Qing; Li, Jiangkuo; Xu, Xiangbin (Frontiers in Nutrition, 2022)
The effect of Sly-miR171e on postharvest cold tolerance of tomato fruit was studied. The present results indicated that overexpression of Sly-miR171e (miR171e-OE) promoted postharvest chilling injury (CI) in red and green stages tomato fruits. Compared with wild type (WT) and miR171e-OE fruit, tomato fruit of knockdown of Sly-miR171e (miR171e-STTM) showed lower CI index, lower hydrogen peroxide (H2O2) content, and higher fruit hardness after harvest. In the miR171e-STTM fruit, the relative expression levels of GRAS24, CBF1, COR, GA2ox1 and the content of GA3 were increased, while the relative expression levels of GA20ox1 and GA3ox1 were decreased. This study indicated that the knockdown of Sly-miR171e improved the postharvest cold tolerance of tomato fruit under low temperature storage, and provided valuable information for genetic modification of miR171e and control of postharvest CI of fruit.